A Case Study of Integrating Interwise: Interaction, Internet Self-Efficacy, and Satisfaction in Synchronous Online Learning Environments - Kuo, Yu-Chun; Walker, Andrew E.; Belland, Brian R.; Schroder, Kerstin E. E.; Kuo, Yu-Tung (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
This paper reports research on the implementation of a web-based videoconferencing tool (Interwise) for synchronous learning sessions on an industrial technology course offered through a university in northern Taiwan. The participants included undergraduate students from the same course offered in two different semesters. We investigated students' perceptions of interactions with the instructor and fellow students, their confidence in utilizing the Internet (Internet self-efficacy), and the satisfaction level that students perceived throughout the learning process with Interwise. We also examined the effect of interactions and Internet self-efficacy on student satisfaction. Data collected through paper-based and online surveys were analyzed using correlation and multiple regression. The results revealed that overall, learners perceived Interwise as a tool that was moderately easy to use for synchronous learning. Learners seemed to prefer using the Interwise features, such as emotion icons, talk, or raise hand, to interact with their instructor. Learners had high confidence in gathering data or getting support through the Internet, but low confidence in resolving Internet related problems. Both learner-learner and learner-instructor interactions were significant predictors of student satisfaction, while Internet self-efficacy did not significantly contribute to satisfaction. Learner-instructor interaction was found to be the strongest predictor of student satisfaction.